Islamic Education Based on Quantum Learning: Conceptual and Methodological Perspective - Abidin, Muhammad Zainal (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
This article aims to compare quantum learning, a new effective approach to education in the Western world, with the philosophy of Islamic education. There were three foci of the literature studied—the human aspect as both the subject and the object of the education, the learning environment, and the learning methodology. This paper is a study of relevant literature of quantum learning and the philosophy of Islamic education. The result of the comparison shows that conceptually the views of quantum learning as it pertains to human beings as both the subject and the object of the education, the learning environment, and learning methods have many similarities with the spirit of Islamic education. In could be viewed that philosophically, quantum learning has a strong foundation in Islamic eduation. Quantum learning is the concrete form of Islamic education, as developed by the Western perspective of education.